Economic Report on Africa 2015 - United Nations (United Nations, 2015)
This report examines and provides analysis on the critical elements of effectively fostering industrialisation and hence structural transformation based on extensive review of experience with industrialised countries and Africas post-independence attempt at industrialisation. Ten country case studies were also conducted to shed light on industrialising through trade. The findings from this exercise inform the policy recommendations contained in this report.